Syndecan-1 (CD138) as a Pathogenesis Factor and Therapeutic Target in Breast Cancer - Sheta, Mona; Götte, Martin (Current Medicinal Chemistry, 2021)
The successive stages of breast cancer growth and dissemination depend on cell-autonomous factors and the communication between tumor cells and their surrounding cellular and extracellular matrix microenvironment. The cell surface heparan sulfate proteoglycan Syndecan-1 is dysregulated both in tumor cells and cells of the breast tumor stroma, indicating a potential role in the pathogenesis of this most frequent malignancy in women. Indeed, Syndecan-1 interacts with numerous ligands and receptors relevant to tumor progression, affecting processes as diverse as cancer stem cell function, cell proliferation, apoptosis, cell adhesion, migration and invasion, tumor angiogenesis, and leukocyte function in the tumor stroma. The present review summarizes the current understanding of breast carcinogenesis in correlation with their Syndecan-1 expression, involved mechanisms, and proposed therapeutic strategies against Syndecan-1-related malignancy.
Keywords: extracellular matrix